Phenomenological approach to applying reflective journaling to experiential learning (Journal of Applied Learning and Teaching, 2021)
The application of unique approaches to experiential education, action learning, active learning, game-based learning, and problem/project-based learning provide an ample suite of examples for architecting reflective thinking and learning. These forms of learning occur to construct of new knowledge within the individual, the team, or the organization. This pursuit of new knowledge is not new but is based upon a new perspective of phenomenology. We need to credit the heritage of spiritually and philosophically grounded phenomenology, which suggests that the tools used today to achieve reflective learning can prove exceptionally valuable.This paper reviews the literature associated with phenomenology-based reflective learning, especially as it has been applied in spiritual communities. Additionally, experientially-based adult learning will be reviewed to establish how phenomenology has been integrated. Our purpose is to introduce an instructional tool that could be easily applied in online or face-to-face classrooms for creating new, useful knowledge from personal learning experiences narrated within reflective learning journals.